Inventory of Data Elements in State and Federal Corrections Information Systems, 1998 - Sabol, William J. ([Verlag nicht ermittelbar], 1999)
This survey summarizes the data elements maintained by state and federal corrections information systems that track adult, sentenced offenders, and assesses the severity of obstacles in reporting statistical information. Two instruments, an Inventory Questionnaire and an Obstacles Survey, were mailed to Departments of Correction in all 50 states and the District of Columbia, and to the Federal Bureau of Prisons. The Inventory Questionnaire asked 207 questions about data elements describing offenders, 15 questions about elements describing facility management, and 20 questions about the capabilities of the information system to process data electronically. For some elements, questions were asked to determine if more detailed information (subvalues) about the element existed. The Obstacles Survey asked departments to rate the severity of problems they may encounter when processing requests for statistical information. The items were grouped into five categories: legislative and institutional factors, hardware factors, software factors, staffing factors, and data factors.